Short Report: Investigation of Dengue and Japanese Encephalitis Virus Transmission in Hanam, Viet Nam - Simmons, Cameron (2018)
This study investigated whether a large dengue epidemic that struck Hanoi in 2009 also affected a nearby semirural area. Seroconversion (dengue virus-reactive immunoglobulin G enzyme-linked immunosorbent assay) was high during 2009 compared with 2008, but neutralization assays showed that it was caused by both dengue virus and Japanese encephalitis virus infections. The findings highlight the importance of continued Japanese encephalitis virus vaccination and dengue surveillance.